2019
DOI: 10.1016/j.cell.2018.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Control of Astrocyte Pathogenic Activities in CNS Inflammation

Abstract: Graphical Abstract Highlights d A multidisciplinary approach to study effects of environmental factors on astrocytes d Linuron boosts IRE1a-XBP1 signaling in astrocytes via Sigmar1 d Astrocytic IRE1a-XBP1 signaling promotes CNS inflammation in EAE d IRE1a-XBP1 signaling is activated in astrocytes in multiple sclerosis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
146
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(150 citation statements)
references
References 111 publications
(97 reference statements)
3
146
0
1
Order By: Relevance
“…In line with the recently discovered cross-talk between microglia and astrocytes during neuroinflammation (Rothhammer et al, 2018;Vainchtein et al, 2018;Wheeler et al, 2019), we observed that LPS injection increased astroglial GFAP reactivity. Based on the detrimental outcome of impaired astrogliosis on axon regeneration (Anderson et al, 2016), this elevated astrocytic response may contribute to restorative mechanisms that support neurological recovery.…”
Section: Discussionsupporting
confidence: 89%
“…In line with the recently discovered cross-talk between microglia and astrocytes during neuroinflammation (Rothhammer et al, 2018;Vainchtein et al, 2018;Wheeler et al, 2019), we observed that LPS injection increased astroglial GFAP reactivity. Based on the detrimental outcome of impaired astrogliosis on axon regeneration (Anderson et al, 2016), this elevated astrocytic response may contribute to restorative mechanisms that support neurological recovery.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our observations, a number of recent studies have shown that microglial cells isolated from AD-like mouse models undergo important metabolic changes with the activation of the HIF pathway [65][66][67]. Furthermore, Hif1 is involved in astrocytes proinflammatory activity [68] and its activity seems to be dysregulated in association with other genes genetically linked to AD risk, suggesting that HIF-1α may be detrimental in AD pathology [66].…”
Section: Discussionsupporting
confidence: 90%
“…This signal can be extracellular (e.g., cytokines, purines, aggregated proteins, and myelin debris), trans‐cellular (e.g., transmembrane adhesion molecules like ephrins or integrins), membrane bound [e.g., phosphatidylserine (Chung et al, )], as well as intracellular (e.g., aggregated proteins, nucleic acids from infecting pathogens, ions like Ca 2+ ), [see (Buffo, Rolando, & Ceruti, ; Cunningham et al, ; Kang & Hebert, ; Sofroniew, ) for review]. Interestingly, a recent study reported that astrocytes are also very sensitive to environmental pollutants (Wheeler et al, ). To sense all these molecular triggers, astrocytes are equipped with a wide range of membrane or intracellular receptors, including G Protein‐coupled receptors (like metabotropic glutamate or P2Y purinergic receptors), ionotropic receptors (e.g., P2X purinergic receptors), multimeric cytokine receptors (e.g., IL6 family receptors), Toll like receptors [although their expression by astrocytes is quite disputed (Cunningham et al, )], or tyrosine kinase receptors (e.g., Epidermal growth factor receptor), [see (Kang & Hebert, ; Verkhratsky & Nedergaard, ) for review].…”
Section: What Are the Molecular Cascades Triggered In Reactive Astrocmentioning
confidence: 99%